Clinical vulnerability for severity and mortality by COVID-19 among users of alcohol and other substances. (June 2021) - Benzano, Daniela; Ornell, Felipe; Schuch, Jaqueline Bohrer; Pechansky, Flavio; Sordi, Anne Orgler; von Diemen, Lisia; Kessler, Felix Henrique Paim
Highlights: Individuals with addiction are susceptible to worse COVID-19 prognosis. Smoking, high blood pressure and respiratory problems are prevalent among substance users. Alcohol, crack cocaine and multiusers had distinct vulnerability factors for COVID-19. Abstract: The COVID-19 pandemic is a public health emergency. Individuals with substance use disorder have a higher risk of infection and may suffer from more severe forms of the disease. Our goal is to investigate the prevalence of risk factors for COVID-19 severity in individuals with different substance use and explore whether specific types of substance are potentially associated with more clinical risk factors which could increase morbimortality in this population. The sample included 821 men hospitalized at an inpatient Addiction unit (305 alcohol users, 233 cocaine/crack users, and 283 multiusers). Data were collected using the Addiction Severity Index version 6. The most prevalent risk factors for COVID-19 severity observed in our sample were: smoking (82.5%), arterial hypertension (26.6%), respiratory problems (23.4%), and history of homelessness (25.1%). Arterial hypertension and cirrhosis occurred more frequently among alcohol users. Multiusers lived in the streets longer and had a higher prevalence of HIV than alcohol users. Overall, 28% of the sample had three or more risk factors. The frequency of risk factors was high and this scenario suggests that these individuals could be more susceptible to worse COVID-19 prognosis. Therefore, prevention strategies directed at specific characteristics of substance users merit attention during the pandemic.